2009
DOI: 10.1128/jcm.01347-08
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Genotyping of Methicillin-Resistant Staphylococcus aureus Isolates by Use of Padlock Probes and Tag Microarrays

Abstract: We developed and tested a ligase-based assay for simultaneous probing of core genome diversity and typing of methicillin resistance determinants in Staphylococcus aureus isolates. This assay uses oligonucleotide padlock probes whose two ends are joined through ligation when they hybridize to matching target DNA. Circularized probes are subsequently amplified by PCR with common primers and analyzed by using a microarray equipped with universal tag probes. Our set of padlock probes includes oligonucleotides targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Long-range PCR and sequencing of a ccrB4 element detected in prototype SCCmec IVE strain AR43/3330.1 likewise demonstrated close identity with S. epidermidis strain ATCC 12228 (data not shown), and two class A mec strains from the 1996 BARG study (BK2391 and BK2539) were also found to possess both ccrB4 and ccrB2. Such examples of multiple or composite SCCmec elements argue strongly against the reliability of using a single locus (e.g., ccrC or ccrB4) for assignment of SCCmec types (18,42,83), due to the heterogeneity and mobility of SCC elements (20,63). For instance, novel SCCmec types involving combinations of ccrC with class B, E, and C1 mec complexes (5B, 5B1, 5E, and 5C1, respectively) have been reported (5,55), but several existing SCCmec typing methods may misclassify these as SCCmec type V, based on the use of ccrC alone for typing (42,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-range PCR and sequencing of a ccrB4 element detected in prototype SCCmec IVE strain AR43/3330.1 likewise demonstrated close identity with S. epidermidis strain ATCC 12228 (data not shown), and two class A mec strains from the 1996 BARG study (BK2391 and BK2539) were also found to possess both ccrB4 and ccrB2. Such examples of multiple or composite SCCmec elements argue strongly against the reliability of using a single locus (e.g., ccrC or ccrB4) for assignment of SCCmec types (18,42,83), due to the heterogeneity and mobility of SCC elements (20,63). For instance, novel SCCmec types involving combinations of ccrC with class B, E, and C1 mec complexes (5B, 5B1, 5E, and 5C1, respectively) have been reported (5,55), but several existing SCCmec typing methods may misclassify these as SCCmec type V, based on the use of ccrC alone for typing (42,47).…”
Section: Discussionmentioning
confidence: 99%
“…A real-time PCR assay utilizing a mixture of TaqMan and minor groove binding probes, and targeting the ccrB regions of SCCmec types I to IV, was published in 2004 by François et al (18). More recently, a novel approach utilizing ccr-specific padlock probes and tag microarray analysis for identification of SCCmec types I to VI has been described (42). A shortcoming of both methods is that they detect only one locus (ccr) and ignore the mec complex altogether, which may result in misclassification, given the growing number of reports describing composite SCCmec elements with multiple ccr loci, ccr loci not linked to the mecA gene, and novel combinations of the mec complex and ccr in SCCmec elements (5,69,83).…”
Section: Discussionmentioning
confidence: 99%
“…These methods are effectively mini-MLSTs, and have proved to have a similar performance to full MLST data for resolving clonal complexes and certain sequence types (STs) (10,12), with the added advantage of using real-time PCR technology for rapid and cost-effective SNP discrimination with simple data analysis software (13)(14)(15). The MRSA typing method used by our laboratory was originally described by Huygens et al (13), and consists of 17 separate SYBR Green-based real-time PCRs, including two assays to confirm MRSA (mecA and nuc), eight assays to discriminate seven informative SNPs (arcC210, tpi241/243, arcC162, gmk318, pta294, tpi36*T, tpi36*C, and pta383), five assays targeting binary genes (pvl, cna, sdrE, pUB110, and pT181), one additional SNP assay (aroE252G) for confirmation of the Queensland CA-MRSA ST93, and one internal control reaction (16S).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance is caused by an alternate penicillin-binding protein (PBP2a) which is encoded by the mecA gene. There are several S. aureus genotyping microarrays [95] which enable the detection of a large number of resistance genes and virulence-associated toxin genes in parallel [52,53,57] as well as further DNA microarrays which focus on the detection of S. aureus resistance genes [54,58,60,62]. A broad range S. aureus genotyping DNA microarray has been designed by Monecke et al [53] based on the ArrayTube platform (see Table 4.2).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%